Calculation Methods for Design Flow of Municipal Drainage in Xuzhou Urban Area - LIU Zhanhui; NIU Pingping; YANG Shipu (Renmin Zhujiang)
The catchment area of municipal drainage is usually less than 2 km2,and there is a standard matching problem with downstream water conservancy drainage.On the basis of engineering examples,the design flow of municipal drainage is calculated by the rainstorm intensity formula method,inference formula method,and comprehensive unit hydrograph method.The change of design flow under the two-dimensional combination of the catchment area and average slope is discussed and analyzed.The results show that for municipal drainage,the design flow calculated by the rainstorm intensity formula method and inference formula method is close to and intersect with each other,both of which are greater than the result of the comprehensive unit hydrograph method.It is concluded that the inference formula method can be used to calculate the design flow of municipal drainage,and the calculation result can check the rainstorm intensity formula method.Although the comprehensive unit hydrograph method cannot be used to calculate the design flow of municipal drainage,the calculation result can provide a reference for the standard matching between design flow of municipal drainage and water conservancy drainage.